2015
DOI: 10.1007/s12011-015-0253-3
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent Effect of Boric Acid on Myogenic Differentiation of Human Adipose-derived Stem Cells (hADSCs)

Abstract: Boron, a vital micronutrient for plant metabolism, is not fully elucidated for embryonic and adult body development, and tissue regeneration. Although optimized amount of boron supplement has been shown to be essential for normal gestational development in zebrafish and frog and beneficial for bone regeneration in higher animals, effects of boron on myogenesis and myo-regeneration remains to be solved. In the current study, we investigated dose-dependent activity of boric acid on myogenic differentiation of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…We used the same dose of dsRNA (0.5 μg/μl dsRNA) for all selected genes, and expression levels of 24 (20.87%) genes did not decrease after RNAi feeding. This phenomenon might have resulted from a dose‐dependent effect, as reported previously in the BPH (Chen et al ., ) and human cells (Apdik et al ., ). In RNAi feeding assays, 0.5 μg/μl dsRNA was not enough to silence some target genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same dose of dsRNA (0.5 μg/μl dsRNA) for all selected genes, and expression levels of 24 (20.87%) genes did not decrease after RNAi feeding. This phenomenon might have resulted from a dose‐dependent effect, as reported previously in the BPH (Chen et al ., ) and human cells (Apdik et al ., ). In RNAi feeding assays, 0.5 μg/μl dsRNA was not enough to silence some target genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further work with Mesenchymal Stem Cells showed that active-NaBC1 enhances cell adhesion determining cellular fate versus osteogenic commitment via crosstalk of NaBC1, Bone Morphogenetic Protein Receptor 1A (BMPR1A) and α 5 β 1 /α v β 3 integrins [ 21 ]. Little is known about B homeostasis and function in mammalian cells, and only one report describes the possible role of boric acid in muscle differentiation from adipose-derived stem cells [ 22 ]. However, due to the particular chemical properties of B, this metalloid is widely used in medicinal chemistry [ 23 ], and several biomaterial-based approaches use B as an intrinsic component of the biomaterial platforms for diverse applications [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…When considered from the point of view, these results are consistent with previous results. 51,52 However, as expected, BA slightly decreased cell viability when its concentration reached 5 and 10 wt % in both of 24 and 48 h. When compared to the control, there was statistical significance among groups PHEMA-5%BA and PHEMA-10%BA (****P < 0.001) for 24 h. The result revealed that the PHEMA/BA composite hydrogels (with BA content of 1 and 3 wt %) can exhibit better cell viability, thus they appeared to be a promising material for future in vivo investigation and application.…”
Section: Indirect Cytotoxicity Testmentioning
confidence: 99%